Removal of a giant left ventricular thrombus after myocardial infarction due to dissection of left anterior descending artery - Seppelt, Philipp; Brcic, Andreas; Karck, Matthias; Szabó, Gábor (Interactive cardiovascular and thoracic surgery, 2017)
Abstract. Left ventricular thrombus is a frequent complication after myocardial infarction and is associated with high risk for arterial embolic complications.
Gesehen am 11.07.2018